Framing the time while designing and conducting reviews: A Focused Mapping Review and Synthesis. Issue 23 (21st December 2021) - Palese, Alvisa; Mansutti, Irene; Visintini, Erica; Caruzzo, Davide; Moreale, Renzo; Longhini, Jessica; Danielis, Matteo
Abstract: Aims and Objectives: To identify the profile of time restrictions and their justifications as reported on a set of published reviews. Background: There is a body of methodological knowledge addressing how to design and perform reviews in their different designs. However, how the time restrictions should be set and the justifications that should be provided have received limited attention to date. Design: A Focused Mapping Review and Synthesis following three steps (Focus, Mapping and Synthesis) was performed on 2021. The ENTREQ checklist was followed to report methods and findings. Methods: All Journal of Clinical Nursing reviews published in online or printed version on 2020 ( n  = 85). Time limits imposed in the literature search, and justifications provided were mapped and synthetised with quantitative and a qualitative analysis. Results: Time restrictions in reviews are not always reported and, when available, reflect three different profiles: (a) including all studies, to provide a comprehensive review; (b) selecting a period, to provide reviews for a contemporary practice; and (b) including only recent studies for reviews reflecting current practice. Reasons justifying time restrictions are not always reported; when documented, justifications regard changes in the practice, in the research or in the theory occurred over time, recent or ongoing. Conclusions: In exploring the date restrictions applied in reviews published over the course of a year, it emerged that the time of access to the sources and the justifications are not always indicated. The attributes of the emerging concepts of "comprehensive reviews, " "contemporary practice reviews" and "current practice reviews" might be further developed to support researchers in selecting an appropriate time frame. Relevance to clinical practice: Reviews require improvements regarding the time restrictions and their justifications. Methodological efforts to standardise the approach ensuring transparency in review protocols and in the following review publication are recommended.